Level of adherence and associated factors among HIV-positive adolescents on antiretroviral therapy in Cameroon. Issue 4 (1st October 2020) - Bongfen, Mbuwir Charlotte; Torpey, Kwasi; Ganle, John; Ankomah, Augustine
Abstract : Aim: Globally, there were over 250 000 new HIV infections among adolescents in 2017, with a higher proportion of these in sub-Saharan Africa. In Cameroon, UNICEF estimated over 4 200 new HIV infections in adolescents in 2015; by 2016, there were over 40 000 adolescents who had HIV. Given that the number of adolescents living with HIV in Cameroon is on the increase, there is a need to better understand the factors influencing adherence to treatment. The objective of this study was to assess the factors associated with adherence among adolescents in Cameroon. Methods: A cross-sectional study was conducted. A total of 460 HIV+ adolescents who were receiving antiretroviral therapy were sampled randomly from nine health facilities. Questionnaires and data extraction forms were used to collect data. Descriptive (frequencies and proportions) and inferential (chi-square and multivariate logistic regression) statistical analyses methods were used to analyse the data. Statistical significance was set at p = 0.05 and 95% confidence level. Results: The level of adherence to antiretroviral therapy among the adolescents was 83%. Twelve out of 30 independent variables examined showed significant statistical association with adherence at the bivariate level. In the multivariable logistic regression analyses, however, only two variables significantly predicted adherence — experiencing side effects (AOR = 2.63; 95% CI = 1.14, 6.09; p = 0.02), and internalized stigma (AOR = 2.51; 95% CI = 1.04, 6.04; p = 0.04). Conclusion: Adherence to treatment among adolescents in Cameroon was found to be suboptimal. There is a need for more individualized, targeted medication counselling for adolescents and their guardians as well as strategies to reduce internalized stigma and improve adherence to antiretroviral treatment.